WORLD CLIMATE: A Role-Play Simulation of Climate Negotiations. (June 2015) - Sterman, John; Franck, Travis; Fiddaman, Thomas; Jones, Andrew; McCauley, Stephanie; Rice, Philip; Sawin, Elizabeth; Siegel, Lori; Rooney-Varga, Juliette N.
Global negotiations to reduce greenhouse gas (GHG) emissions have so far failed to produce an agreement. Even if negotiations succeeded, however, a binding treaty could not be ratified or implemented in many nations due to inadequate public support for emissions reductions. The scientific consensus on the reality and risks of anthropogenic climate change has never been stronger, yet public support for action in many nations remains weak. Policymakers, educators, the media, civic and business leaders, and citizens need tools to understand the dynamics and geopolitical implications of climate change. The WORLD CLIMATE simulation provides an interactive role-play experience through which participants explore these issues using a scientifically sound climate policy simulation model. Participants playing the roles of negotiators from major nations and stakeholders negotiate proposals to reduce GHG emissions. Participants then receive immediate feedback on the implications of their proposals for atmospheric GHG concentrations, global mean surface temperature, sea level rise, and other impacts through the C-ROADS (Climate Rapid Overview and Decision Support) policy simulation model used by negotiators and policymakers. The role-play enables participants to explore the dynamics of the climate and impacts of proposed policies using a model consistent with the best available peer-reviewed science. WORLD CLIMATE has been used successfully with students, teachers, business executives, and political leaders around the world. Here, we describe protocols for the role-play and the resources available to run it, including C-ROADS and all needed materials, all freely available atclimateinteractive.org . We also present evaluations of the impact of WORLD CLIMATE with diverse groups.